Contemporary Culture New Directions in Arts and Humanities Research - Zijlmans, Kitty; Zwijnenberg, Robert; Thissen, Judith (Amsterdam University Press, 2013)
Are the humanities still relevant in the twenty-first century? In the context of pervasive economic liberalism and shrinking budgets due to a deep and prolonged recession, the exigency of humanities research for society is increasingly put into question. This volume claims that the humanities do indeed matter by offering empirically-grounded critical reflections on contemporary cultural practices, thereby opening up new ways of understanding social life and new directions in humanities scholarship.